2016
DOI: 10.1111/jfb.13099
|View full text |Cite
|
Sign up to set email alerts
|

Fatty‐acid biomarkers and tissue‐specific turnover: validation from a controlled feeding study in juvenile Atlantic croaker Micropogonias undulatus

Abstract: Fatty-acid (FA) profiles of liver and muscle tissue from juvenile Atlantic croaker Micropogonias undulatus were examined over a 15 week diet-switch experiment to establish calibration coefficients (CC) and improve understanding of consumer-diet relationships for field applications. Essential FAs [docosahexaenoic acid (DHA), 22:6n-3 and eicosapentaenoic acid (EPA) , 20:5n-3] decreased and 18:2n-6 increased in tissues of M. undulatus fed diets with increasing proportions of terrestrial v. marine lipid sources. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…For example, when examining uptake rates of terrestrial (C 18 ) FA, Copeman et al (2013) found an uptake rate of ALA of 0.6-0.13% per day in the liver and 0.021% per day in the muscle of juvenile gadids Pacific cod (Gadus microcephalus) and Walleye Pollock (Theragra chalcogramma). This is similar to the uptake rates of LA reported by Mohan et al (2016) in juvenile Atlantic croaker (Micropogonias undulates). However, variation between diets was found with Atlantic croaker fed a mixed diet showing higher uptake rates (0.09% per day for liver, 0.02% per day for muscle) compared to fish fed on a terrestrial diet (0.02% per day for liver and 0.01% per day for muscle).…”
Section: Vertebratessupporting
confidence: 88%
See 2 more Smart Citations
“…For example, when examining uptake rates of terrestrial (C 18 ) FA, Copeman et al (2013) found an uptake rate of ALA of 0.6-0.13% per day in the liver and 0.021% per day in the muscle of juvenile gadids Pacific cod (Gadus microcephalus) and Walleye Pollock (Theragra chalcogramma). This is similar to the uptake rates of LA reported by Mohan et al (2016) in juvenile Atlantic croaker (Micropogonias undulates). However, variation between diets was found with Atlantic croaker fed a mixed diet showing higher uptake rates (0.09% per day for liver, 0.02% per day for muscle) compared to fish fed on a terrestrial diet (0.02% per day for liver and 0.01% per day for muscle).…”
Section: Vertebratessupporting
confidence: 88%
“…This is similar to the uptake rates of LA reported by Mohan et al . () in juvenile Atlantic croaker ( Micropogonias undulates ). However, variation between diets was found with Atlantic croaker fed a mixed diet showing higher uptake rates (0.09% per day for liver, 0.02% per day for muscle) compared to fish fed on a terrestrial diet (0.02% per day for liver and 0.01% per day for muscle).…”
Section: Synthesis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method produces quantitative estimates of diet composition, with associated measures of precision, and the estimates are pertinent to a longer period of time than estimates obtained using many other methods (Budge, Iverson, & Koopman, 2006). Sampling can be nonlethal and requires only the collection of a relatively small portion of fat tissue, although lipid stratification and the region of the body sampled can be important with some species (e.g., Guerrero et al, 2016;Lambert, Meynier, Donaldson, Roe, & Morel, 2013;Mohan, Mohan, Connelly, Walther, & McClelland, 2016). Diet estimation usually involves a relatively large number of fatty acids, which allows the contribution of a corresponding number of prey types to be estimated and greatly reduces the problem of underdetermined systems common with stable isotope models (Brett, 2014;Phillips & Gregg, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In feeding trials, calibration coefficient estimates have been found to vary by the species of the consumer and various aspects of feeding trial design (e.g., Budge, Penny, & Lall, 2011;Rosen & Tollit, 2012;Thiemann, Iverson, & Stirling, 2008;Wang et al, 2010). Further, fatty acids may be deposited or turnover at different rates in different tissues (Mohan et al, 2016;Nordstrom et al, 2008), and diet composition, physiological state, and the age of an animal can affect fatty acid metabolism (Williams & Buck, 2010). Designing a feeding trial to develop calibration coefficients that are robust to so many factors is complex and perhaps not even feasible.…”
Section: Introductionmentioning
confidence: 99%